An unusual cause of small bowel obstruction caused by a Richter's-type hernia into the urinary bladder - Sakai, Naomi S. (Elsevier, 2014)
INTRODUCTION: The authors present an unusual case of small bowel obstruction in a 62-year-old man. PRESENTATION OF CASE: A 62-year-old man with a background of transitional cell carcinoma (TCC) of the bladder presented to the emergency department with abdominal pain, distension, vomiting and had not opened his bowels for three days. 3 weeks previously he had a repeat Transurtheral resection of bladder tumour (TURBT), during which there was an iatrogenic perforation of the bladder. A CT scan of the abdomen and pelvis revealed small bowel obstruction but did not identify a cause. At laparotomy the cause of the obstruction was identified as a section of the small bowel that had partially herniated into the bladder, via the perforation. The defect was repaired and the patient made an uneventful recovery. DISCUSSION: Herniation of the bowel into a defect in the bladder wall is a rare event with only 6 previous cases reported in the literature. It can cause signs and symptoms of bowel obstruction. CONCLUSION: In patients with known bladder perforations who present with symptoms and signs of bowel obstruction, bowel herniation into the bladder should be considered. Early surgical intervention may be necessary if the patient is clinically unwell with appropriate symptoms and signs and imaging does not provide conclusive answer.